The Differential Diagnostic Value of the Callosal Angle and Evans Index in Mild Cognitive Impairment and Alzheimer's Disease - Liu, Mengqi; Zhang, Jing; Zong, Linxiong; Fan, Wenping; Wang, Botao; Chen, Zhiye (Current Medical Imaging, 2021)
Background: Callosal Angle (CA) and Evans Index (EI) are considered as imaging biomarkers to diagnose normal-pressure hydrocephalus using traditional MR measurement methods. Objective: The current study aimed to evaluate the differential diagnostic value of CA and EI in Mild Cognitive Impairment (MCI) and Alzheimer’s Disease (AD). Methods: Five-hundred and two subjects were selected from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database, which included 168 Normal Controls (NC), 233 MCI and 101 AD patients. The structural MR images were interactively applied with multiplanar reconstruction to measure the CA and EI. Results: CA presented no significant difference among NC, MCI and AD groups (H value = 3.848, P value = 0.146), and EI demonstrated higher value in MCI and AD groups than that in NC groups (P = 0.000 and 0.001, respectively). MCI group had significant larger EI (0.29±0.04) than (0.27±0.03) NC group in 70-75 years old sub-groups. ROC showed that the area under the curve was 0.704±0.045 for NC-MCI in 70-75 years old groups. The correlation analysis indicated that EI was significantly negatively related to MMSE scores of MCI patients (r = -0.131, P = 0.046). Conclusion: EI might serve as a screening imaging biomarker for MCI in 70-75 years old patients, and show limited differential value for the diagnosis of AD. CA could present no diagnostic value for MCI and AD in the current study.
Keywords: evans index